2013
DOI: 10.1063/1.4820563
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel production from waste cooking oil catalyzed by solid acid SO42−/TiO2/La3+

Abstract: A solid acid catalyst SO42−/TiO2/La3+ was prepared via sol-gel method using tetrabutyl titanate as TiO2 precursor. The catalyst simultaneously catalyzed esterification and transesterification resulting in the synthesis of biodiesel from waste cooking oil with high content of free fatty acids as feedstock. The optimization of reaction conditions was also performed. The maximum yield of more than 90% could be obtained under the optimized conditions that catalyst amount 5 wt. % of oil, 10:1 molar ratio (methanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…/MCM-41 (MCM) which were prepared according to the published procedures. 28,29 The results are exhibited in Fig. 2.…”
Section: àmentioning
confidence: 96%
“…/MCM-41 (MCM) which were prepared according to the published procedures. 28,29 The results are exhibited in Fig. 2.…”
Section: àmentioning
confidence: 96%
“…Among these, sulphated doped TiO2 is a good example of a solid super-acidic catalyst which is also used in the petrochemical industry and petroleum refining process [24,47] and showed better performances as compared to other sulphated metal oxides. This is due to the acid strength of the TiO2 particles which further enhances with loading of SO groups on the surface of TiO2 [48]. Many recent studies have reported that the super acidity of sulphated titanium dioxide catalysts could be based on Lewis acid and Br nsted acid sites, and the formation of Br nsted acid sites are possibly due to the higher content of sulphate groups in the catalyst [24,49,50].…”
Section: Introductionmentioning
confidence: 99%
“…, could enhance the catalytic stability of the sulphated TiO2 for the simultaneous esterification and transesterification of waste cooking oil [48,58]. The application of such catalysts is preferable in simultaneous esterification and transesterification reactions when using cheap raw materials with high FFA due to the high acidity of solid acid catalysts.…”
Section: +3mentioning
confidence: 99%
“…A solid acid catalyst SO 4 2− /TiO 2 /La 3+ catalyzed both the esterification and transesterification of waste cooking oil with high content of free fatty acids ( Figure 9) [27]. Under the optimized conditions (catalyst amount 5 wt.% of oil, 10:1 molar ratio methanol to oil, temperature 110 °C and reaction time of 1 h) biodiesel was obtained with more than 90% of yield.…”
Section: So 4 2− /Tio 2 /La 3+mentioning
confidence: 99%